Snapshots of modern life: impressionism between reality, photography and color (Itinera, 2022)
The essay aims to investigate the ways in which Impressionist art participates in socio- cultural modernity. Emancipation from the academic tradition, the choice of subjects from everyday reality, the influence of photography and the study of color are some of the elements through which the Impressionists investigated the reality of their time.